THE PATTERNS OF RADICALISM ANTICIPATION BASED ON COMMUNITY IN INDONESIA - Nispul Khoiri Khoiri; Asmuni Asmuni (State Islamic University of North Sumatra Indonesia, 2020)
The study departs from an important question of how the situation and conditions of development of radicalism in Indonesia. How do radicalism group strategies strengthen social networks? How is the urgency and effectiveness of handling community-based radicalism? How is the pattern of handling anticipation of community-based radicalism? Research with descriptive type and method used is a qualitative method with naturalistic logical phenomena and social psychology approaches. The results showed that the situation and conditions of the development of radicalism in Indonesia remain vigilant, this group is like a fire in the husk, this group has never died and Indonesia is the basis for the growth and development of radicalism compared to other ASEAN countries. There are various patterns of handling anticipated community-based radicalism carried out in Indonesia, namely: Through social organizations, social and religious organizations, youth organizations, various forums with the aim of deterring radicalism and terrorism and other organizations. Through active community involvement without being organized by anyone. it is carried out through families, educational institutions, da'wah movements, mosque empowerment, commemorative and historic holidays, performances of arts and creativity performances, social media and local wisdom. Keywords: The Patterns of Radicalism, Anticipation Based on Community, North Sumatra and West Java Provinces